Pain Relief After Knee Arthroscopy: Intra-articular Morphine, Intra-articular Bupivacaine, or Subcutaneous Morphine?: Intra-articular Morphine, Intra-articular Bupivacaine, or Subcutaneous Morphine?. Issue 3 (May 1997) - Cepeda, Soledad M.; Uribe, Carlos; Betancourt, Jairo; Rugeles, Jose; Carr, Daniel B.
Abstract : Background and Objectives: This investigation was undertaken to compare analgesic effects, side effects, and requirements for supplemental analgesic therapy after knee arthroscopy in patients given intra-articular (IA) or subcutaneous (SC) morphine, intra-articular bupivacaine, or placebo. Methods: In a randomized, double-blind controlled trial, 112 patients, 14-65 years old each received two solutions, one SC and the other IA. Group IAM (n = 30) received 10 mg IA morphine in 20 mL normal saline plus 1 mL of SC normal saline Group IAB (n = 27) received 20 mL IA bupivacaine 0.5% with IA epinephrine plus 1 mL SC normal saline Group SCM (n = 26) received 20 mL IA normal saline plus 10 mg SC morphine in 1 mL. Group P (n = 29) received 20 mL IA normal saline plus 1 mL SC normal saline. Pain was evaluated on arrival in the postanesthesia care unit (PACU), and 30, 45, 60, 90, and 120 minutes afterwards. If pain exceeded 4/10 on a visual analog pain scale in the PACU, 30 mg intravenous ketorolac was given, and if pain persisted, 0.4 mg hydromorphone was added every 7 minutes. After PACU discharge, patients whose pain exceeded 4/10 received oral ketorolac 10 mg every 6 hours; oral acetaminophen plus codeine was added every 4 hours if pain still exceeded 4/10. Analgesic requirements, along with visual analog pain score, sedation, and nausea were recorded every 6 hours for 72 hours. Results: All three active (nonplacebo) pain treatments provided good pain control in the PACU. Side effects were similar in all groups. The placebo group had higher pain scores at 120 minutes ( R = .02), higher supplemental analgesic requirements at 60 minutes ( P = .04) and 90 minutes ( P = .02) and the highest amount of total opioid rescue dose ( P = .04). Patients in groups IAB and P had higher visual analog pain scores at 6 hours ( P = .04) and 30 hours ( P = .049) than those in Groups IAM and SCM. Conclusion: A single 10-mg dose of morphine given either IA or SC provides better and longer-lasting postoperative pain relief after knee arthroscopy than 20 mL IA bupivacaine 0.5% with epinephrine.